A critical reading of gender construction in Malaysian children's literature - Nair, Ramesh; Talif, Rosli (Cambridge University Press, 2013)
Children's literature is an important resource for knowledge construction among young children. As they read the stories or have the stories read to them, children are presented with multiple ideologies and belief systems and this includes notions of masculinity and femininity (Taylor, 2003: 301). These ideologies are absorbed by young children and go on to influence their attitudes and behaviour as they participate in society. Perhaps for this reason, the reading of gender in children's literature has been an area that has drawn the interest of numerous researchers over the decades (Bender and Lach, 1990; Collins, Ingoldsby & Dellman, 1984; Crabb & Bielawski, 1994; Dellmann-Jenkins, Florjancic & Swadener, 1993; Desai, 2001; Dutro, 2002; Gooden & Gooden, 2001; Kortenhaus & Demarest, 1993; Oskamp, Kaufman & Wolterbeck, 1996; Poarch & Monk-Turner, 2001; Turner-Bowker, 1996; Weitzman et al., 1972). These studies have generally pointed to evidence of sexism, that is, the denigration of females realised in tandem with the exaltation of males (Ivy & Backlund, 1994: 72).